초등학교 저학년 여학생의 성 성숙과 신체상 및 자아존중감에 관한 연구 - 노소영(So Young Roh); 김계하(Kye Ha Kim) (지역사회간호학회지, 2012)
Purpose: The purpose of this study was to examine the sexual maturation, body image, and self-esteem of Korean elementary school girls with symptoms of precocious puberty compared to those with no symptoms of precocious puberty. Methods: The subjects were 309 girls of lower grades in elementary school. Tanner's Sexual Maturation Rating (SMR), Self Image Scale, and Self-esteem Scale were utilized to determine the presence of symptoms of precocious puberty, body image, and self esteem. Collected data were analyzed by Chi-square test, independent t-test, and one-way ANOVA using the SPSS/WIN 17.0 program. Results: The percentage of the girls with breast development was 14.9%. Breast development usually began in the third grade (56.5%). Of the subjects, 0.3% were experiencing menstruation. Breast development was related to grade, age, height, weight, and a cause of worry. There was a significant difference of body image between girls with breast development in the first grade and in the second grade. Conclusion: An effective intervention that can improve the self-image of children with symptoms of precocious puberty should be developed to prevent and treat physical and mental problems related to sexual maturation.